Divine Battles in the Akkadian Period - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
The Akkadian period saw the emergence of an unusual theme that was to disappear in the following periods, that of battles between the gods. The motif is seen on about 70 or so cylinder seals, and is characterised by refined style and execution, designed to stir the emotions. Based on an analysis of seals and inscriptions, this paper aims to understand what audience this theme was intended for, why it appears in this era only to disappear subsequently and what its meanings are.